Safety Management of Trans Java Toll Road Using Vision Zero Approach - Hikaru, Revi (Kirana Publisher (KNPub), 2025)
The Ngawi-Kertosono Toll Road, part of Indonesia's Trans-Java network, is critical for regional mobility but suffers from high accident rates due to factors like speeding and human error. This study analyzes accident data from 2020-2023, identifying key black spots with significant Equivalent Accident Numbers (EANs) that exceed safety thresholds. Recommendations include infrastructure improvements, enhanced driver education, and the adoption of advanced technologies, aligned with the Vision Zero strategy aimed at eliminating traffic fatalities. The findings emphasize a comprehensive approach involving stakeholder coordination to effectively address safety challenges and reduce accidents on this vital roadway.